2020
DOI: 10.1111/jfpp.14468
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance in vancomycin‐resistant lactic acid bacteria (VRLAB) isolated from foods of animal origin

Abstract: In this study, antibiotic resistance in 47 vancomycin‐resistant lactic acid bacteria (VRLAB), isolated from 340 foods of animal origin obtained in Turkey, were investigated. VRLAB isolates were molecularly identified as Enterococcus gallinarum (44.68%), Pediococcus pentosaceus (25.53%), P. acidilactici (12.77%), E. casseliflavus (6.38%), E. casseliflavus/E. gallinarum (4.26%), Weissella cibaria (2.13%), W. confusa (2.13%), and W. minor (2.13%). The disk diffusion test results showed that 57.45%, 53.19%, 44.68%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 69 publications
2
10
0
Order By: Relevance
“…According to earlier research, the possibility of high natural resistance of Weissella species to quinolones (nalidixic acid), glycopeptides (vancomycin and teicoplanin), and aminoglycosides (except high‐level resistance encoded by aminoglycosides plasmidic modifying enzymes) can be found in different LAB species with a restricted horizontal transfer to other bacterial species (Ammor et al., 2007 ; Danielsen & Wind, 2003 ; Flórez et al., 2016 ; Imperial & Ibana, 2016 ; Jeong & Lee, 2015 ; Mathur & Singh, 2005 ; Toomey et al., 2010 ). Results of susceptibility and resistance for the tested antibiotics on the Weissella strains were consistent with previous studies (Akpınar Kankaya & Tuncer, 2020 ; Lee et al., 2012 ; Patel et al., 2012 ). The disk diffusion method can be applied for fast screening of strains, whereas the MIC assessment is the commonly accepted antibiotic resistance determination method for LAB.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…According to earlier research, the possibility of high natural resistance of Weissella species to quinolones (nalidixic acid), glycopeptides (vancomycin and teicoplanin), and aminoglycosides (except high‐level resistance encoded by aminoglycosides plasmidic modifying enzymes) can be found in different LAB species with a restricted horizontal transfer to other bacterial species (Ammor et al., 2007 ; Danielsen & Wind, 2003 ; Flórez et al., 2016 ; Imperial & Ibana, 2016 ; Jeong & Lee, 2015 ; Mathur & Singh, 2005 ; Toomey et al., 2010 ). Results of susceptibility and resistance for the tested antibiotics on the Weissella strains were consistent with previous studies (Akpınar Kankaya & Tuncer, 2020 ; Lee et al., 2012 ; Patel et al., 2012 ). The disk diffusion method can be applied for fast screening of strains, whereas the MIC assessment is the commonly accepted antibiotic resistance determination method for LAB.…”
Section: Discussionsupporting
confidence: 91%
“…Until today, the investigation of antibacterial resistance profiles of the genus Weissella is limited to few published reports (Akpınar Kankaya & Tuncer, 2020 ; Ayeni et al., 2011 ; Fhoula et al., 2018 ; Jeong & Lee, 2015 ; Lee et al., 2012 ; Muñoz‐Atienza et al., 2013 ; Patel et al., 2014 ). In this context, antimicrobial susceptibility testing can be used as required selection criterion for probiotic cultures as well as a useful guide for precise antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data of this study showed that vancomycin‐resistant all Enterococcus and 13 Pediococcus isolates carry one or more virulence genes and the most of them strong or moderate biofilm producer. In addition, our previous study (Akpınar Kankaya & Tuncer, 2020) exhibited that these VRLAB strains contain several transferable antibiotic resistance genes. Although LAB accepted generally recognized as safe, the risk should not be ignored that virulence factors and transferable antibiotic resistance genes containing LAB isolates may directly or indirectly threat consumer health.…”
Section: Discussionmentioning
confidence: 94%
“…A total of 47 VRLAB were isolated from 340 foods of animal origin (85 raw milk and dairy products, 85 red meat and meat products, 85 chicken and chicken products, 85 sea fish) and they were molecularly identified as 26 Enterococcus (21 Enterococcus gallinarum , 3 Enterococcus casseliflavus , 2 Enterococcus casseliflavus/Enterococcus gallinarum ), 18 Pediococcus (12 Pediococcus pentosaceus , 6 Pediococcus acidilactici ), and 3 Weissella (1 Weissella cibaria , 1 Weissella confusa , 1 Weissella minor ) previously by Akpınar Kankaya and Tuncer (2020). Bacterial cultures were grown in de Man Rogosa and Sharpe (MRS) broth (LAB M Ltd.) at 37°C for 18 hr.…”
Section: Methodsmentioning
confidence: 99%